Socialization of the Negative Impact of Online Gambling on Adolescent Academic Achievement - Rumadi, Rumadi; Purborini, Vivi Sylvia (Civiliza Publishing, 2024)
Gambling has been known as a form of entertainment activity that involves betting financial value. Education is one of the important instruments in efforts to prevent and overcome online gambling problems among teenagers. Schools, as formal educational institutions, have a crucial role in providing an understanding of the law and legal consequences of online gambling practices to teenagers. This socialization activity is in the form of a seminar on zoom by making thorough preparations. the phenomenon of online gambling carried out by teenagers has many negative impacts, both in terms of social, religious, material, academic achievement and also psychological